An Examination of the Differential Impacts of Social Bonds and Organized Crime Affiliation on Male and Female Youth Street Gang Members' Delinquency. Issue 1 (2nd January 2022) - Hong Chui, Wing; Vinod Khiatani, Paul; Kiconco, Milliam
ABSTRACT: This study examines the differential impacts of social bonds and organized crime affiliation on theft and violence in a sample of 201 male and female youth street gang members in Hong Kong. Specifically, the study examines gender differences in social bonds and delinquency among active youth street gang members aged between 12 and 24 years. A purposive sample of 109 male and 92 female active youth street gang members was recruited from a public housing estate with the help of outreach social workers. A series of hierarchical regression analyses indicated that parental attachment, involvement in organizations, and Hong Kong triad affiliation were associated with theft and violence among male youth street gang members, while belief in the legal system and Hong Kong triad affiliation were associated with theft among female youth street gang members. However, only the effect of the belief social bond on (non-)violent delinquency was found to be significantly different between male and female youth street gang members. Peer attachment was not significantly associated with theft nor violence among male or female youth street gang members. Subsequently, implications for social service delivery and future studies are discussed.